Determining the 94Ins/DelATTG Promoter Polymorphism in the Transcription Factor NF-Kb in Patients with Popliteal Aneurysm - Mirzaie, M.; Fatehpur, S.; Guliyev, Z.; Schulz, S.; Reichert, S. (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
Background: Popliteal aneurysms, with a frequency of 85% of all peripheral aneurysms, have a poor prognosis with a high amputation frequency. Up to now, the -94Ins/DelATTG promoter polymorphism in the transcription factor NF-KB has been assumed to be involved in its pathophysiology. Aims: The aim of this study was to investigate the role of this genetic variant in patients with popliteal aneurysm. Patients and Methods: In total, 48 patients with popliteal aneurysm (44 males, mean age 74.5 years) and 49 healthy controls (19 males, 51.5 years) were enrolled in the study. The duplex sonographic diagnosis of popliteal aneurysm was verified in each patient by CT an-giography. Popliteal aneurysms were diagnosed when the diameter of the affected vessel was at least 15 mm. In subjects of the control group, duplex examination excluded the diagnosis of popliteal aneurysm. Smoking history, arterial hypertension, diabetes mellitus, hyperlipoproteinemia (HLP), hyperuricemia, coronary heart disease (CHD) and carcinoma were recorded as comorbidities. For the NF-KB polymorphism, the -94Ins/DelATTG polymorphism (rs28362491) in the NF-KB gene was investigated. Results: With 50.5%, the id genotype of -94Ins/DelATTG polymorphism was the most frequently encountered genotype (46.9% in the control group versus 54.2% in patients with popliteal aneurysm). At second position, the genotype ii followed with 35.1% (36.7% in the control group versus 33.3% in patients with popliteal aneurysm) and genotype dd with 14.4% (16.3% in the control group versus 12.5% in patients with a popliteal aneurysm). However, there was no significant difference in the distribution of genotypes. In the case of allele distribution, with 60.2% for allele i in the control group and 60.4% for allele i in patients with a popliteal aneurysm, and for allele d in 39.8% of the control group and 39.6% in patients with a popliteal aneurysm no significant differences could be found. Binary logistic regression analysis showed a clear association only between male gender and smoking with popliteal aneurysm but not for the -94Ins/ DelATTG genotypes. Conclusion: In contrast to male gender and smoking habits, no significant differences in the geno distributions of -94Ins/DelATTG polymorphism were detected with respect to the diagnosis of popliteal aneurysms.